Centrifugal separations in molecular and cell biology - Birnie, G. D.; Rickwood, D. (David) (Butterworths, 1978)
Centrifugal Separations in Molecular and Cell Biology focuses on the application of modern centrifugation technology in molecular and cell biology, including the separation and fractionation of biological particles by centrifugation on the preparative and analytical scales.